PHASE SHIFT INFLUENCE RESEARCH OF THE REFERENCE OSCILLATOR SIGNAL ON THE OUTPUT SIGNAL IN HOMODYNE DEMODULATION SCHEME - Volkov, A V; Oskolkova, E S; Plotnikov, M Y; Mekhrengin, M V; Shuklin, P A (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2015)
Subject of Research. Important feature of homodyne demodulation method based on the arctangent function approach is the phase shift between the reference oscillator signal and the interference signal. This phenomenon is caused by propagation delays of impulses in the optical interferometric sensor scheme and the analog low-pass filter in front of the phase modulator which produces the reference oscillator signal phase delay. There is multiplying of the reference oscillator signal and the interference signal in this homodyne demodulation scheme during its processing, and the phase shift between these signals leads to a distortion of the output signal. This paper deals with the findings of the phase shift influence of the reference oscillator signal by the output signal of the demodulation scheme at various parameters of the interference signal. Estimation of required accuracy is given of the phase shift compensation for the specified level distortion of the output signal. Method. Mathematical model is proposed in MATLAB. In this model, interference signal with changing parameters by a set of rules is passed through the considered demodulation scheme. This gives the possibility to obtain the dependences of the output signal amplitude from the reference oscillator signal phase shift, the operating point of the interferometer, the depth of phase modulation and amplitude of the measured phase signal. Results obtained during the simulation showed the need to compensate the reference oscillator signal phase shift. To assess this shift in the current homodyne demodulation scheme the original method of its determination has been proposed. The method is based on the transmission of the interference signal and the oscillator signal via one and the same band-pass filter that separates the phase modulation carrier frequency. According to the phase delay between the receiving signals, the value of the reference oscillator signal phase shift can be judged on. This shift can be corrected with knowledge of the value of the reference oscillator signal phase shift. Correction is achieved by making the required delay in reference oscillator signal. Main Results. The results of mathematical modeling show significant nonlinear dependences of the output signal on the reference oscillator signal phase shift at different values of the phase modulation depth, the operating point of the interferometer and the measured phase signal amplitude. It was found out that optimal values of the reference oscillator signal phase shift equal to 0, 180 and 360 provide minimum distortions of the output signal. It was shown that to achieve about 4% distortion level of the output signal phase shift compensation with an accuracy of 3% relative to period of the reference oscillator signal was required. Practical Significance. The original method making it possible to assess the value of the reference oscillator signal phase shift has been proposed. The reference oscillator signal phase shift compensation during considered homodyne demodulation scheme practical implementation provides the correctness of the scheme operation and increases the signal to noise ratio of the output signal.